Influence of seismic strain rates on the co‐ and post‐seismic response of civil engineering buildings. (26th July 2020) - Astorga, Ariana; Guéguen, Philippe
Summary: The elastic properties of buildings change during earthquakes. In particular, fundamental frequencies are observed to shift rapidly during the co‐seismic phase and to recover slowly once the strong motion has finished. Although the frequency shift is usually correlated with loading amplitude, the co‐seismic frequency variations observed in real structures are not only determined by the absolute amplitude of the strain value. In order to interpret the uncertainties of the prediction of engineering demand parameters for a given intensity measure, we analyze the influence of loading rates (i.e., strain rates) on resonance frequency variations in buildings with different structural states during the loading and unloading phases caused by seismic events. Our observations suggest the existence of a strain rate threshold that activates the nonlinear response of the structure, characterizing the activation of cracking and indicating a strong nexus between the elastic structural response, structural state, and the loading process.